Differences in the breeding performance of great tits Parus major between a forest and an urban area: a long term study on first clutches. Issue 1 (1st January 2020) - Wawrzyniak, J.; Glądalski, M.; Kaliński, A.; Bańbura, M.; Markowski, M.; Skwarska, J.; Zieliński, P.; Bańbura, J.
Abstract: The great tit Parus major inhabits various types of forests, yet it prefers deciduous forests. In the urbanized areas it is one of the commonest bird species, even where only isolated trees are present, which seems to be a relatively recent phenomenon. This paper presents results of a long-term study (2002–2015) of variation in reproductive performance (number of hatchlings, hatching success, number of fledglings, fledging success, breeding success and nest failure rate) in first clutches of two great tit populations nesting in two contrasting habitats: a mature deciduous forest and an urban parkland, in central Poland. This study shows a clear and sustained spatial pattern of variation where the forest population of great tits produced more hatchlings and fledglings per successful nests than the urban park site population. Breeding success and fledging success demonstrate a similar but slightly less obvious pattern, with higher values for the forest site than the urban parkland area occurring consistently in the vast majority of years. Also hatching success was generally slightly higher in the forest than in the urban park but did not show such a clear spatial pattern. Only the nest failure rate was higher in the forest than in the urban parkland. We suggest that caterpillar richness in the forest compared to the urban parkland is one of the key drivers of the observed differences in the breeding performance between the study habitats. We also found positive correlations between fledgling numbers and caterpillar abundance and between fledgling numbers and mean May temperatures in the forest, whereas neither breeding nor fledging success showed such correlations. In the urban parkland, fledgling numbers as well as fledging and breeding successes were positively correlated with mean May temperatures. The between-population variation we found probably reflects a more general difference between urban and forest populations of tits.